Plasmacytoid Dendritic Cells Depletion and Elevation of IFN-γ Dependent Chemokines CXCL9 and CXCL10 in Children With Multisystem Inflammatory Syndrome - Caldarale, Francesca; Giacomelli, Mauro; Garrafa, Emirena; Tamassia, Nicola; Morreale, Alessia; Poli, Piercarlo; Timpano, Silviana; Baresi, Giulia; Zunica, Fiammetta; Cattalini, Marco; Moratto, Daniele; Chiarini, Marco; et al. (Frontiers in immunology, 2021)
SARS-CoV-2 occurs in the majority of children as COVID-19, without symptoms or with a paucisymptomatic respiratory syndrome, but a small proportion of children develop the systemic Multi Inflammatory Syndrome (MIS-C), characterized by persistent fever and systemic hyperinflammation, with some clinical features resembling Kawasaki Disease (KD). With this study we aimed to shed new light on the pathogenesis of these two SARS-CoV-2-related clinical manifestations. We investigated lymphocyte and dendritic cells subsets, chemokine/cytokine profiles and evaluated the neutrophil activity mediators, myeloperoxidase (MPO), and reactive oxygen species (ROS), in 10 children with COVID-19 and 9 with MIS-C at the time of hospital admission. Patients with MIS-C showed higher plasma levels of C reactive protein (CRP), MPO, IL-6, and of the pro-inflammatory chemokines CXCL8 and CCL2 than COVID-19 children. In addition, they displayed higher levels of the chemokines CXCL9 and CXCL10, mainly induced by IFN-γ. By contrast, we detected IFN-α in plasma of children with COVID-19, but not in patients with MIS-C. This observation was consistent with the increase of ISG15 and IFIT1 mRNAs in cells of COVID-19 patients, while ISG15 and IFIT1 mRNA were detected in MIS-C at levels comparable to healthy controls. Moreover, quantification of the number of plasmacytoid dendritic cells (pDCs), which constitute the main source of IFN-α, showed profound depletion of this subset in MIS-C, but not in COVID-19. Our results show a pattern of immune response which is suggestive of type I interferon activation in COVID-19 children, probably related to a recent interaction with the virus, while in MIS-C the immune response is characterized by elevation of the inflammatory cytokines/chemokines IL-6, CCL2, and CXCL8 and of the chemokines CXCL9 and CXL10, which are markers of an active Th1 type immune response. We believe that these immunological events, together with neutrophil activation, might be crucial in inducing the multisystem and cardiovascular damage observed in MIS-C.